Being a Disabled Patient: Negotiating the Social Practices of Hospitals in England - Read, Stuart (Social Inclusion, 2018)
Accessing hospital care and being a patient is a highly individualised process, but it is also dependent on the culture and practices of the hospital and the staff who run it. Each hospital usually has a standard way of ‘doing things’, and a lack of flexibility in this may mean that there are challenges in effectively responding to the needs of disabled people who require ‘reasonably adjusted’ care. Based on qualitative stories told by disabled people accessing hospital services in England, this article describes how hospital practices have the potential to shape a person’s health care experiences. This article uses insights from social practice theories to argue that in order to address the potential problems of ‘misfitting’ that disabled people can experience, we first need to understand and challenge the embedded hospital practices that can continue to disadvantage disabled people.